Nutritional characterization of the extrusion-processed micronutrient-fortified corn snacks enriched with protein and dietary fiber - Shah, Faiz-ul-Hassan; Sharif, Mian Kamran; Ahmad, Zulfiqar; Amjad, Adnan; Javed, Muhammad Sameem; Suleman, Raheel; Sattar, Dur-e-Shahwar; Amir, Muhammad; Anwar, Muhammad Junaid (Frontiers in Nutrition, 2022)
Study was planned to develop protein and dietary fiber enriched micronutrient fortified corn snacks using extrusion technology. Micronutrient (Fe, Zn, I, vitamin A and C) Fortified extruded snacks were developed using corn, soybean and chickpea flour followed by characterization for their nutritional attributes. Supplementation of soybean and chickpea was done discretely (20-40 g/100g) or in combination of both (10:10, 15:15 and 20:20 g/100g). Corn snacks having 40g/100g soy flour showed best nutrient profile with maximum percent increase in protein (171.9%) and fiber (106%) as compared to the snacks developed using chickpea and/or mixed supplementation of soy and chickpea. Total dietary fiber (18.44±0.34%), soluble dietary fiber (10.65±0.13%) and insoluble dietary fiber (7.76±0.38%) were also found highest in the soy supplemented snacks (40 g/100g). It was noted that 100g consumption of corn snacks can fulfill 115-127%iron, 77-82%zinc, 90-100%vitamin A and 45-50% RDA of Vitamin C. Amino acids extrusion processing results in 2.55-45.1% reduction in essential amino acids with maximum in cysteine and minimum in valine whereas, leucine and tryptophan remain fairly stable during extrusion.